Synthesis of Cobalt Ferrite Nanoparticles Using Microemulsion Method: Structure, Morphology, and Magnetic Properties (Journal of Engineering Science, 2022)
Cobalt ferrite nanoparticles were prepared by the microemulsion method. Different values of pH of the microemulsion were maintained to find out the optimum pH to prepare cobalt ferrite nanoparticles. Prepared nanoparticles were characterized using X-ray Powder Diffraction (XRD), Vibrating Sample Magnetometer (VSM), and Scanning Electron Microscope (SEM). Rietveld refinement was used to analyze the crystal structure of the prepared cobalt ferrite nanoparticles. The crystallite size of prepared nanoparticles has been found from XRD in the range of 13.79 nm to 30.40 nm. The saturation magnetization, remanent magnetization, and coercivity have been found to be 12.05 emu/g, 0.77 emu/g, and 118.912 Oe respectively from VSM measurements.Journal of Engineering Science 13(1), 2022, 81-87